Endoscopic ultrasonography shear wave as a predictive factor of endocrine/exocrine dysfunction in chronic pancreatitis. Issue 2 (17th June 2020) - Yamashita, Yasunobu; Tanioka, Kensuke; Kawaji, Yuki; Tamura, Takashi; Nuta, Junya; Hatamaru, Keiichi; Itonaga, Masahiro; Ida, Yoshiyuki; Maekita, Takao; Iguchi, Mikitaka; Kitano, Masayuki
Abstract: Background and Aim: Chronic pancreatitis (CP) leads to permanent impairment of exocrine and endocrine functions. The endoscopic ultrasonography (EUS)‐based Rosemont classification plays an important role in diagnosing CP. However, it is based on subjective judgment. In contrast, EUS shear wave measurement (EUS‐SWM) has been established to be a precise method for evaluating tissue hardness. This study aimed to evaluate the utility of EUS‐SWM in diagnosing CP and determining exocrine and endocrine dysfunctions. Methods: We evaluated 40 patients who underwent EUS‐SWM between January 2019 and January 2020. They were classified into the normal pancreas and early, probable, and definite CP groups following the Japan Pancreatic Society criteria. EUS‐SWM value was compared between the normal pancreas group and the early, probable, and definite CP groups. The relationship between EUS‐SWM value and exocrine/endocrine dysfunctions was also assessed. The cut‐off value of EUS‐SWM for diagnosing CP and exocrine/endocrine dysfunctions was investigated. Results: The EUS‐SWM value was positively correlated with the Japan Pancreatic Society criteria stages. The probable and definite CP groups had significantly higher EUS‐SWM values than the normal group. The areas under the receiver operating characteristic curve for the diagnostic accuracy of EUS‐SWM for CP, exocrine dysfunction, and endocrine dysfunction were 0.92, 0.78, and 0.63, respectively. The cut‐off values of 1.96, 1.96, and 2.34 for diagnosing CP, exocrine dysfunction, and endocrine dysfunctions had 83%, 90%, and 75% sensitivity, respectively, and 100%, 65%, and 64% specificity, respectively. Conclusions: Endoscopic ultrasonography shear wave measurement provides objective assessment and can thus be an alternative diagnostic tool for diagnosing CP and exocrine/endocrine dysfunctions.